ANALISIS EFEKTIVITAS PERAN PEMERINTAH DALAM MENURUNKAN ANGKA KEMISKINAN (KAJIAN DI KABUPATEN PIDIE JAYA) - Baihaqi Baihaqi (STISNU Aceh, 2022)
Based on data released by BPS, the percentage of poverty in Pidie Jaya until the end of 2020 has not shown a significant decline. It is also influenced by various factors. The purpose of this study was to determine the role of government and the effectiveness of government programs and to determine the obstacles faced by the government in reducing poverty. Because this research is a qualitative research which analyzed descriptively, primary data can be obtained directly by interviewing several sources including the head of Baitul Mal, the Baitul Mal Secretariat in Pidie Jaya, Bappeda Employees and the PKH Committee in Pidie Jaya. While the secondary data is obtained by examining documentation in the form of books, journals, articles, websites and other research results as well as other relevant documents to help answer the problem formulation through the data. In addition, the authors also analyze the data that the authors get from internal data from various government agencies in Pidie Jaya. The technique that the writer uses to collect all the data is the technique of observation, interviews, and documentation. The results show that the government in reducing poverty has made various policies and roles, to optimize the performance in collaboration with several agencies such as Baitul Mal, Social Service, Bappeda and Public Works Office. It cannot be denied, that the data released by BPS shows a negative trend, however, various efforts and programs that have been carried out by the local government to reduce poverty have not been effective and in fact the program has not had optimal implications. Of course, this condition is influenced by several obstacles, including human resources, facilities and infrastructure, lack of employment opportunities, ineffective performance of state apparatus and assistance that is not well targeted.